2023
DOI: 10.1001/jamanetworkopen.2022.52698
|View full text |Cite
|
Sign up to set email alerts
|

Association of Patient Proximity to Dermatologic Care With Melanoma Stage at Diagnosis and Outcome

Abstract: This cohort study evaluates the association of proximity to dermatologic clinicians with stage at diagnosis and cancer-specific survival among adults with cutaneous melanoma in Iowa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…The goal of this study is to investigate if there is an association between metastatic melanoma response to checkpoint inhibitor therapy and tumor-infiltrating lymphocyte (TIL) classification on primary cutaneous melanoma biopsies [1]. While some studies revealed no link between a patient's proximity to dermatology care and the stage of melanoma diagnosis, others proposed that a closer distance to such services may lead to earlier detection of the condition [2]. This information can help to distinguish melanoma from nevi.…”
Section: Literature Surveymentioning
confidence: 99%
“…The goal of this study is to investigate if there is an association between metastatic melanoma response to checkpoint inhibitor therapy and tumor-infiltrating lymphocyte (TIL) classification on primary cutaneous melanoma biopsies [1]. While some studies revealed no link between a patient's proximity to dermatology care and the stage of melanoma diagnosis, others proposed that a closer distance to such services may lead to earlier detection of the condition [2]. This information can help to distinguish melanoma from nevi.…”
Section: Literature Surveymentioning
confidence: 99%